FEATURES OF GROUP MOTIVATION FOR CRIMINAL ACTIONS - Спицька, Ліана; Данченко, Тетяна (SWorldJournal, 2024)
The emergence and realization of motives for criminal activity largely depend on whether the crime is committed individually or in a group. This circumstance leaves a significant imprint on a subject’s motivation and the manifestation of social determinan